IMPLEMENTASI PERATURAN WALIKOTA SURABAYA NOMOR 25 TAHUN 2016 TENTANG TATA CARA PEMBERIAN DAN PERTANGGUNGJAWABAN HIBAH DAN BANTUAN SOSIAL - Idrus . (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
The method used in this research is qualitative research method (qualitative research). Qualitative research is a study aimed at describing and analyzing phenomena, events, social activities, attitudes, perceptual beliefs, thoughts of individuals individually or in groups. The population in this study consisted of: 1) Head of Surabaya City Social Service, 2) Head of Surabaya City Social Service UPTD, 3) Implementer, 4) Beneficiary. The sampling technique used